MIAT promotes tumor-infiltrating CD8+ T-cell exhaustion and malignant progression of renal cell carcinoma via activating JAK3/STAT3 pathway - Bin Wang; Jian-Feng Wang; Jun-Hang Luo; Ming-xiao Zhang; Lan-yu Jing; Hao-tian Tan; Zi-ran Dai; Da-zhi Long; Han-chao Liu; An-ze Yu; Zi-yin Chen; Zhen-hua Chen (Journal for ImmunoTherapy of Cancer)
Background The hyporesponsiveness of tumor-infiltrating exhausted CD8+ T cells to tumor cells contributes to immune escape of renal cell carcinoma (RCC), representing a major challenge in current immunotherapy. However, the underlying molecular mechanism of CD8+ T-cell exhaustion in the tumor microenvironment remains largely unknown.Methods We first examined myocardial infarction associated transcript (MIAT) expression in RCC cell lines and clinical specimens, and analyzed its correlation with CD8+ T-cell exhaustion markers. To investigate the immunoregulatory role of MIAT, we evaluated its effects on CD8+ T-cell function using T-cell co-culture systems and humanized-peripheral blood mononuclear cells RCC patient-derived xenograft models. To determine the direct effects of MIAT on tumor cells, we assessed RCC cell malignant phenotypes following MIAT knockdown both in vitro and in immunodeficient nude mouse orthotopic xenograft models. Mechanistically, we employed RNA fluorescence in situ hybridization, chromatin isolation by RNA purification followed by mass spectrometry, RNA immunoprecipitation, and chromatin immunoprecipitation assays to identify the molecular interactions between MIAT, transcription factors, and target genes.Results MIAT was highly expressed in RCC cells and positively correlated with CD8+ T-cell exhaustion status. MIAT knockdown significantly enhanced CD8+ T-cell function with increased perforin and interferon-γ production, while reducing the expression of exhaustion markers programmed cell death protein 1 and T-cell immunoreceptor with Ig and ITIM domains. Mechanistically, MIAT was predominantly localized in the nucleus and formed a trimeric complex with transcription factor ETS proto-oncogene 1 (ETS1) and janus kinase 3 (JAK3) promoter, thereby upregulating JAK3 expression and activating the JAK3/signal transducer and activator of transcription 3 (STAT3) signaling pathway. Importantly, ectopic expression of JAK3 largely abolished both the tumor-suppressive effects and enhanced T-cell function induced by MIAT depletion.Conclusions Our study demonstrates that the MIAT/JAK3/STAT3 pathway plays a critical role in malignant progression and immune escape of RCC through regulating CD8+ T-cell exhaustion, suggesting its potential as a therapeutic target for RCC immunotherapy.